The contribution of fine motor skills and isometric hand strength to competitive archery performance: A cross-sectional study - Kalkavan, A.; Kavalci, I.; Kayikçioglu, N. A. (International Journal of Kinesiology & Sports Science, 2025)
Background: Upper extremity strength and motor coordination are critical components of archery performance, especially among youth athletes. However, limited research has examined the specific contributions of hand grip strength and hand dexterity to shooting success in young archers.